Bali’s Ethnic Arts Industry:: Crafting Global Identities Amidst a National Tourist Agenda - Esperanza, Jennifer (Material Culture Review)

(untitled) (National Museums of Canada, 2010)
Abstract This article is based on fieldwork in Tegallalang, a village in Bali, Indonesia, that mass produces and exports Native American dream catchers, Australian Aboriginal didgeridoo, African masks and other "ethnic" objects for the global marketplace. For most of the 20th century and beyond, Dutch colonials and Indonesian nationalists have urged the Balinese to stage cultural production, performance and a particular view of "authenticity" as a means of advancing specific colonial/national agendas. Bali has often been used as an example of a "last paradise" where tradition must be preserved while the rest of the Indonesian state modernizes its political and economic agendas. This article explores Tegallalang’s ethnic arts industry as a platform from which the Balinese have been able to counter the stereotypes of a province bound by unchanging aesthetic styles and cultural traditions. While Bali’s cultural tourism industry continues to rely heavily upon notions of a Hindu culture unaffected by global processes and modernizing economies, the ethnic arts industry allows local producers to assert more complex, cosmopolitan identities for themselves.